2015
DOI: 10.1186/s13104-015-1531-z
|View full text |Cite
|
Sign up to set email alerts
|

Australian GP management of osteoarthritis following the release of the RACGP guideline for the non-surgical management of hip and knee osteoarthritis

Abstract: BackgroundOsteoarthritis (OA) is a highly disabling and costly condition with an escalating prevalence in Australia due to the ageing and increasing obesity of the population. The general practitioner (GP) plays a central role in the management of this condition. The aim of this study was to examine opinions about the management of OA by Australian GPs following the release of the Royal Australian College of General Practitioners Guideline for the non-surgical management of hip and knee OA (RACGP OA CPG), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 24 publications
3
41
2
Order By: Relevance
“…Existing studies have shown that SMRR not only can prevent OA cartilage degeneration through antioxidative stress but can also reduce OA cartilage damage and thus be used to treat OA [20,28]. The effective active SMRR component-target gene relationship network showed that the treatment of OA by SMRR is achieved through multiple components, multiple pathways, and multiple targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have shown that SMRR not only can prevent OA cartilage degeneration through antioxidative stress but can also reduce OA cartilage damage and thus be used to treat OA [20,28]. The effective active SMRR component-target gene relationship network showed that the treatment of OA by SMRR is achieved through multiple components, multiple pathways, and multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, in abnormal circumstances, SMRR can interfere with OS [18,19]. It has been claimed that SMRR can prevent articular cartilage degeneration in OA rabbits by inhibiting OS [20]. In addition, SMRR can alleviate OA by inhibiting NF-κB signal transduction and regulating the JAK2/STAT3 and AKT signal transduction pathways [21].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of these guidelines on the prescribing practices of general practitioners, where the majority of prescribing in Australia occurs, has yet to be elucidated. Following the release of the 2009 guidelines an increase in prescribing of potent opioids to future TJR patients was observed for reasons that remain unclear. Utilization of non‐pharmacological treatments including physiotherapy and weight loss as first‐line strategies are low compared to pharmacological management rates for osteoarthritis .…”
Section: Discussionmentioning
confidence: 99%
“…In most countries, people with knee OA are managed predominantly in primary care by their GP or family doctor [ 9 ]. Optimal care requires patients to be empowered to self-manage with lifestyle interventions that require long-term behavioural change, which creates additional management challenges for GPs [ 10 , 11 ]. Unsurprisingly, current management of the condition can be variable and is often inconsistent with recommended practice [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal care requires patients to be empowered to self-manage with lifestyle interventions that require long-term behavioural change, which creates additional management challenges for GPs [ 10 , 11 ]. Unsurprisingly, current management of the condition can be variable and is often inconsistent with recommended practice [ 3 , 11 , 12 ]. Studies from many parts of the world reveal over-reliance on imaging and drugs compared with self-management and lifestyle options [ 13 ], and referrals to orthopaedic surgeons can be higher than referrals for exercise [ 13 ].…”
Section: Introductionmentioning
confidence: 99%